(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The present research is focused on two classified American and Italian diplomatic documents that point out the injunctions on the activity of the foreign diplomatic missions in Bucharest exercised by the Romanian Government (Securitate) and to the infringement of the diplomatic immunities and privileges by the same Government. There are described the spying techniques through wiretaps (45 microphones) and environmental recordings. The documents focuses on the direct pressures on the American diplomats and on the service passport staff in order to cooperate with the Securitate and the disappearance of 30 Romanian citizens who worked for the foreign diplomatic missions in Bucharest. The abuses were so great that the head of the Italian Legation in Bucharest asked the change of the whole staff and officials.